Multifunctional Plants: Ecosystem Services and Undervalued Knowledge of Biocultural Diversity in Rural Communities—Local Initiatives for Agroecological Transition in Chile - Peredo-Parada, S; Barrera-Salas, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
With the aim of contributing to the understanding of plants’ multifunctionality for sustainable agroecosystem management, the first part of this paper addresses the importance of functional biodiversity in the design of agroecological systems, including the local context in the generation of situated knowledge. The second part describes three participatory research experiences with local farmers across three locations in Chile. The first experience reports on the use of Dasyphyllum diacanthoides (endemic tree) as fodder. A second experience focuses on the establishment of Rosa spp. (invasive species) as an agroforestry system integrated into the landscape. Both experiences were collaborative efforts with farmer communities of the Andean Mountains in southern Chile. The final experience describes the use of different spontaneous aromatic and medicinal plants through biological corridors to encourage beneficial insects as natural controllers. All three research experiences reveal a lack of knowledge, decontextualization, and undervaluation of the biocultural diversity present in some traditional Chilean agroecosystems. © 2023 by the authors.